Model Development for Analyzing the Distribution Patterns of Nitrogen Dioxide Using Sentinel-5P Satellite Data in Thailand - Hemwan , Phonpat; Montien-art , Sitinat; Charoenpanyanet , Arisara (Burapha Science Journal, 2026)
Nitrogen dioxide (NO2) is one of air pollution that Thailand has been affected for many years. The aims of this study are separated into two objectives. First, to explain the situation of nitrogen dioxide concentration in spatial temporal and analyze the relationship of factors affecting that led to generation of nitrogen dioxide using by spatial statistic. Secondly, finding a suitable model to be estimated the concentration of nitrogen dioxide from Sentinel-5P data and ground station data using linear regression model during January 2019 to December 2020 in Thailand. As a result, the average of nitrogen dioxide concentration in 2019 has higher than the nitrogen dioxide concentration in 2020 the value was 10.95 ppb and 10.67 ppb respectively. The maximum total annual average of nitrogen dioxide concentration occur during Dry season (between November and April) in January 2019 (18.37 ppb) the minimum average occur during Wet season (between May and October) in June 2020 (8.05 ppb). In addition, the regions with the highest average of nitrogen dioxide concentration was central region during the 4th week of January 2019 (40.69 ppb) and the lowest average concentration of nitrogen dioxide was found in northern region during the first week of September 2019 (2.84 ppb). The suitable model for estimating the concentration of nitrogen dioxide was Cubic model with coefficient of determination (R2) at 0.72 and it model accuracy overall was 70.29 %